TINJAUAN FILOSOFIS TUJUAN PENDIDIKAN ISLAM, PENDIDIK, DAN ANAK DIDIK - Lydia Sartika (Jurnal At-Tabayyun, 2019)
This study aims to determine the philosophical review of the objectives of Islamic education, educators, and students. The purpose of education is something to be achieved by educational activities or efforts. If education is in the form of formal education, the objectives of that education must be reflected in a curriculum. If the purpose of education is based on the Qur’an, then the aim of education in question is the goal of Islamic education, which is an absolute requirement in defining education itself at least based on basic concepts of man, nature and science as well as considering the basic principles of the Qur’an. From the perspective of Islamic education philosophy, researchers rely more on murabbi because it leads to maintenance, both physical and spiritual. Researchers understand that murabbi also means maintaining and maintaining the nature of students before adulthood, developing all potential towards perfection, directing all nature towards perfection, and carrying out education gradually. Meanwhile, students are individuals who are growing and developing physically, psychologically, socially, and religiously in navigating their life in this world and in the hereafter. In this study, researchers used qualitative research, in which research with a qualitative approach was an attempt to find the truth in a field by finding the strength or capacity in each concept. Qualitative research is also a research method used in revealing problems that exist in the work life of government, private, community, youth, women, sports, arts and culture organizations so that they can be used as a policy for the common welfare. That’s why researchers used qualitative research methods and approaches.